FACTORS OF SPEAKING ANXIETY IN ENGLISH ACADEMIC PRESENTATION - Hermawan, Didit; Susilawati, Endang; Surmiyati, Surmiyati (Universitas Tanjungpura, 2024)
This qualitative study aimed to investigate the underlying causes of English-Speaking anxiety experienced by third-year English education students at Universitas Tanjungpura when presenting academically. A descriptive approach was employed to identify these factors based on the self-reported experiences of high-anxiety students. Seven participants were selected through a preliminary questionnaire and were subsequently interviewed to gather in-depth data. Frequency distribution analysis was conducted to analyze the collected data. The findings revealed three primary factors contributing to speaking anxiety: communication apprehension, test anxiety, and fear of negative evaluation. Of these, communication apprehension emerged as the most significant factor, exerting a substantial influence on students' anxiety levels. Test anxiety and fear of negative evaluation also played notable roles in contributing to overall anxiety. These results highlight the multifaceted nature of English-Speaking anxiety and underscore the need for targeted interventions to address these specific factors and support students in overcoming their fears and developing effective communication skills.